A Novel tool for sustainability assessment of energy projects - Sukumaran, Sreenath; Sudhakar, Kumarasamy; Ahmad Fitri, Yusop (2021)
A single sustainable performance index to measure the holistic performance of energy system has been formulated. This product is capable to overcome the drawbacks in performance assessment method of the available products. Technical elements in the tool have null upfront cost.